Assessing the Sealing Performance and Clinical Outcomes of Endodontic Treatment in Patients with Chronic Apical Periodontitis Using Epoxy Resin and Calcium Salicylate Seals - Horhat, Razvan Mihai; Bumbu, Bogdan Andrei; Orel, Laura; Velea-Barta, Oana; Cirligeriu, Laura; Chicin, Gratiana Nicoleta; Pricop, Marius; Rivis, Mircea; Dinu, Stefania; Horhat, Delia Ioana; Bratosin, Felix; Fericean, Roxana Manuela; et al. (Medicina (Kaunas, Lithuania), 2023)
Background and Objectives: Recognizing the significance of a hermetic apical seal for successful root canal treatment, the present investigation aimed to evaluate two sealing materials through an in vitro analysis, as well as to ascertain the clinical outcomes of patients treated with these two sealers in an in vivo setting. Materials and Methods: For the in vitro part of the study, two control groups of thirty monoradicular teeth were obturated with two sealers. Then, the sealers’ performance was tested based on a predefined protocol. Group A included 30 patients treated with an epoxy oligomer resin-based sealer (Adseal, MetaBiomed), while Group S comprised 30 patients treated with a polymeric calcium salicylate-based sealer (Sealapex, Kerr). Samples were sectioned and evaluated under the microscope to determine the sealer’s tightness by measuring the dye penetration into the root canal filling. For the in vivo part, a prospective study was designed to include 60 patients with chronic apical periodontitis in two endodontic treatment groups, using the same two sealers. Results: The in vitro analysis found that dye penetration in Group A was 0.82 mm (±0.428), while in Group S, the dye penetration was statistically significantly deeper, being 1.23 mm (±0.353). In the in vivo part of the study, the periapical index (PAI) significantly decreased 6 months after endodontic treatment, with 80.0% of patients in Group A having a PAI score of 2 compared to only 56.7% in Group S (p-value = 0.018). Similarly, tooth mobility scores significantly decreased after treatment, but with no difference between groups. The marginal bone loss decreased significantly more in the Adseal group compared to the Sealapex group (23.3% vs. 50.0%, p-value = 0.032). At the same time, 40.0% of patients in Group S had failed tooth healing compared to only 13.3% in Group A (p-value = 0.048). Conclusions: The in vitro study showed that Adseal had a better sealing capacity and a lower degree of dye penetration compared to Sealapex. However, on clinical evaluation in the in vivo study, both patient groups exhibited significant improvements in periapical index, tooth mobility scores, and pain reduction following endodontic treatment. Nevertheless, patients treated with Adseal showed a significantly greater improvement in PAI values, tooth mobility, and teeth healing after treatment. Overall, Adseal, as an endodontic sealer, may provide better sealing capabilities and enhanced clinical outcomes in the treatment of chronic apical periodontitis.